Microsoft Project 2021 for beginners. (Packt Publishing, 2023)
Microsoft Project Standard is a project management solution designed to be installed on a desktop. It supports schedule development, budgeting, task management, and reporting. Microsoft Project is designed to help users set realistic goals for project teams and customers by creating schedules, distributing resources, managing budgets, helping users create projects, tracking tasks, and reporting results. In this introduction to Project 2021, we will understand core project functionality and its advantages. The course begins with an introduction to Project 2021 and explains the new features, project plans, and costs. The course advances to getting familiar with Project and Project ribbons and commands, the Quick Access toolbar, keyboard shortcuts, views, and tables. We will advance to set up a project and create, save, open, and close a project, project calendars, and define exceptions. We will create tasks, automatic and manual, milestones, subtasks, and summaries, and use Work Breakdown Structure. We will develop material resources and add to tasks. We will explore tables and project views. We will understand basic reporting, export reports to other formats, and handle project security. Upon completion, we will independently create projects, manage and secure them using Project 2021 and easily create decision-making reports. What You Will Learn Explore the differences between Project plans and Project versions Understand the Project interface and quickly find commands Understand the difference between automatic/manual scheduled tasks Manage task and project progress, create and format basic reports Assign lag or lead time, task deadlines, constraints, task resources Create a work breakdown structure, link tasks, and add dependencies Audience If you are an individual, project manager, or a PMO looking to take your project management skills to the next level, or if you are an individual using Project 2019 or older but want to upgrade to the latest version from Microsoft to upgrade your skills in project management, then this course is for you. There are no prerequisites; however, having a project management background or some experience using older versions of Project will be an advantage. About The Author Simon Sez IT: Simon Sez IT has offered technical courses for individuals, small businesses, and Fortune 500 companies since 2008, with thousands of employees who can benefit from the easy-to-learn and hands-on software training. It offers over 8,000 video tutorials on a range of software programs. Simon Sez IT ensures stress-free eLearning and enhanced employee productivity--whether you implement new software or a technological upgrade in your work environment. With over 600,000 students from 180 countries, Simon Sez IT is the preferred online learning choice for individuals and businesses worldwide.